Handbook on crime and technology - Hummer, Don; Byrne, James M. (Edward Elgar Publishing, 2023)
Examining the consequences of technology-driven lifestyles for both crime commission and victimization, this comprehensive Handbook provides an overview of a broad array of techno-crimes as well as exploring critical issues concerning the criminal justice system's response to technology-facilitated criminal activity.The Handbook adopts a unique three-fold typology of technology-enabled crime: techno-crime committed by professional criminals (crime as work), techno-crime committed in traditional workplace settings (crime at work), and techno-crime committed by individuals outside of traditional workplace settings (crime after work.) Chapters explore an extensive range of criminal activities facilitated by the digital age, from embezzlement, financial fraud, corporate espionage, phishing, and ransomware to identity theft, hacking, cyber terrorism, and internet sex and hate crimes. Looking to the future, the Handbook considers timely questions posed by our continued reliance on information technology, including whether we are in danger of becoming a global surveillance state and how we might prevent the facilitation of cyber terrorism by social media giants.This dynamic Handbook will be an invaluable resource for scholars and students interested in criminology, digital sociology, terrorism and security, and surveillance studies. Offering practical insights on the need for a coordinated global techno-crime control strategy, it will serve as a resource for policymakers seeking cutting edge solutions to the growing problem of techno-crime